Journalistic ethics in the covering of violence - Mac Gregor, Felipe (1991)
​This article reviews the legal dispositions that regulates the activity of the mass media in Peru. It also analyses how the mass media can help to combat violence, and how the mass media can auto-regulate its policies concerning the covering of violence. The author argues in favor of an Association-Academy responsible for the supervision of these policies.